Bacillus subtilis engineered for aerospace medicine: a platform for on-demand production of pharmaceutical peptides - Vallota-Eastman, Alec; Bui, Cynthia; Williams, Philip M.; Valentine, David L.; Loftus, David; Rothschild, Lynn (Frontiers in Space Technologies, 2023)
Biologics, such as pharmaceutical peptides, have notoriously short shelf lives, insufficient for long-duration space flight missions to the Moon or Mars. To enable the sustainable presence of humans on the Moon or Mars, we must develop methods for on-site production of pharmaceutical peptides in space, a concept we call the Astropharmacy. Here, we present a proof-of-concept for the first step needed: a low-mass system for pharmaceutical production designed to be stable in space. To demonstrate feasibility, we engineered strains of the space-hardy spore-forming bacterium, Bacillus subtilis, to secrete two pharmaceutical peptides important for astronaut health: teriparatide (an anabolic agent for combating osteoporosis) and filgrastim (an effective countermeasure for radiation-induced neutropenia). We found that the secretion peptides from the walM and yoqH genes of B. subtilis worked well for secreting teriparatide and filgrastim, respectively. In consideration of the Translational Research Institute for Space Health (TRISH) challenge to produce a dose equivalent in 24 hours, dried spores of our engineered strains were used to produce 1 dose equivalent of teriparatide from a 2 mL culture and 1 dose equivalent of filgrastim from 52 mL of culture in 24 hours. Further optimization of strain growth conditions, expression conditions, and promoter sequences should allow for higher production rates to be achieved. These strains provide the template for future optimization efforts and address the first step in the Astropharmacy, capable of on-site production, purification, and processing of biopharmaceutical compounds in platforms amenable for use in space.